(3JaSjQ bhdg JYGdi (B" (3cfJ cfRG eMajkG (B"s - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3hbhdg SHMGfg hJYGdi (B" (3cfJ cfRkG eMajkG (B" (3aCMHHJ Cf CYQa s
(3BNQgG (B:s
(3hGeJO cdGeg Edi Cf CPf GdXgQ abGd GdZRGdi LGA GdMb hRgb GdHGWd abGe hNQL ef YfOg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B352 - (3U(B353s
(3GfXQg eY GdeNWhW Qbe (B292s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs